L’Arlequinade anglaise et la gravure satirique au XVIIIe siècle : Élaboration esthétique et détournement politique - Marc Martinez (Revue LISA)
In the satirical texts of the 1720s, the English pantomime and its emblematic figure, Harlequin, pandered to the xenophobic prejudices that stigmatised foreignness and at the same time fuelled the attacks of literary satirists who exposed the degeneracy of the national stage. The print market that was developing around the same period issued a series of satirical engravings that endlessly rework the æsthetic grievances of verbal satire and give concurrently to the figure of Harlequin a political significance. From being the satirical embodiment of a perverted theatrical taste, Harlequin becomes a grotesque metaphor of the figures and fixtures of political life. Alongside the ideological import, these prints reflect the aesthetic elaboration of contemporary graphic satire. While these engravings invite a mode of viewing that moves from the image to the printed word, they translate the stylistic strategies of verbal satire into graphic form and oscillate between the emblematic tradition and the mimetic mode.